FUNDAMENTALS OF THE DEVELOPMENT OF THE DIGITAL ECONOMY IN THE CONDITIONS OF THE ECONOMY OF UZBEKISTAN (Intent Research Scientific Journal, 2023)
This article focuses on the development of the digital economy in the territory of the Republic of Uzbekistan and the elimination of existing problems, the use of the conveniences and new opportunities of the digital economy at the state level, the need for our country to be among the developed countries, the investment policy of commercial banks and the incomparable value of the digital economy in all areas. it is about the place.